2013
DOI: 10.1016/j.jpsychires.2013.03.012
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal sequencing of nicotine dependence and bipolar disorder in the national epidemiologic survey on alcohol and related conditions (NESARC)

Abstract: Bipolar disorder (BD) and nicotine dependence (ND) often co-occur. However, the mechanisms underlying this association remain unclear. We aimed to examine, for the first time in a national and representative sample, the magnitude and direction of the temporal relationship between BD and ND; and to compare, among individuals with lifetime ND and BD, the sociodemographic and clinical characteristics of individuals whose onset of ND preceded the onset of BD (ND-prior) with those whose onset of ND followed the ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Though it has been suggested that smoking may contribute to the development of the bipolar disorder (Slyepchenko, Brunoni, McIntyre, Quevedo, & Carvalho, 2016 ), the evidence of smoking as a risk factor for bipolar disorder is still scarce (Martínez-Ortega et al, 2013 ; Vermeulen et al, 2021 ). It is a previously well-described observation that persons with bipolar disorders tend to smoke (Heffner et al, 2011 ; Lasser et al, 2000 ) and the association between smoking and mood stabilizers found in this study, with a sevenfold increase in risk after adjustment for all confounders, suggests that smoking may be a risk factor for bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though it has been suggested that smoking may contribute to the development of the bipolar disorder (Slyepchenko, Brunoni, McIntyre, Quevedo, & Carvalho, 2016 ), the evidence of smoking as a risk factor for bipolar disorder is still scarce (Martínez-Ortega et al, 2013 ; Vermeulen et al, 2021 ). It is a previously well-described observation that persons with bipolar disorders tend to smoke (Heffner et al, 2011 ; Lasser et al, 2000 ) and the association between smoking and mood stabilizers found in this study, with a sevenfold increase in risk after adjustment for all confounders, suggests that smoking may be a risk factor for bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these high rates, few prospective studies investigate smoking as a potential risk factor for bipolar disorder. Smoking may play a mediating role in the severity of bipolar disorder (Thomson et al, 2015 ), and nicotine dependence and bipolar disorder were found in one study to predict the onset of each other (Martínez-Ortega et al, 2013 ). Also, a recent Mendelian randomization study concluded that smoking can be viewed as a causal risk factor for developing bipolar disorder (Vermeulen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Associations between unipolar or bipolar depression and cigarette smoking may be due to biological and social-environmental factors that increase the risk of both disorders, smoking to reduce psychiatric symptoms, effects of nicotine or smoke exposure on the development of these disorders, or bidirectional causality. 81 82 83 84 85 Like smokers with schizophrenia, smokers with unipolar depression indicate that they smoke primarily to cope with craving and negative affect, and secondarily for pleasure. 62 However, they are as worried as smokers without depression about the effects of smoking on their health and equally motivated to quit.…”
Section: Unipolar and Bipolar Depressionmentioning
confidence: 99%
“…8 Smoking is two to three times more common in BP compared to the general population, 25 and although smoking initiation usually precedes BP, there seems to be a complex bidirectional causality. [26][27][28] It has been postulated that coffee drinking is associated with decreased risk of MD, especially among those with high caffeine intake. 5,29 However, previous evidence is based on mostly cross-sectional studies with adult populations alone.…”
Section: Limitationsmentioning
confidence: 99%
“…While the association between smoking and depression has been widely studied, current knowledge is scarce for BP 8 . Smoking is two to three times more common in BP compared to the general population, 25 and although smoking initiation usually precedes BP, there seems to be a complex bidirectional causality 26–28 …”
Section: Introductionmentioning
confidence: 99%